Students profile of adversity quotient in mathematics learning: Control, origin and ownership, reach, and endurance - Ega Gradini; Julia Noviani (American Journal of STEM Education, 2024)
This study aims to map high school students’ Adversity Quotient (AQ) profile in mathematics learning from the perspective of Control, Origin and Ownership, Reach, and Endurance (CO2RE) dimensions. Data were collected from 168 tenth-grade students in mathematics classes from six senior high schools in Aceh Tengah, Indonesia. The students' AQ was measured using the Adversity Response Profile in Mathematics Learning (ARP-ML). The ARP-ML consisted of 20 items with an equal distribution for each CO2RE subconstruct and used a 5-point Likert scale for each item. The study results showed that AQ significantly and positively correlates with mathematics achievement. Students with higher AQ tend to have higher mathematics achievement, and vice versa. The Adversity Quotient profile of students is dominated by moderate and low AQ (50% and 45%, respectively), with only 5% of the students having higher AQ. Higher AQ students have higher Control (C), Origin and Ownership (O2), Reach (R), and Endurance (E) than the Moderate and Low AQ students. These findings imply that students with higher AQ tend to have high mathematics achievement. Therefore, educators, parents, and other stakeholders need to develop students' AQ to facilitate their achievement of improved outcomes in mathematics learning.